Pengaruh Model Kooperatif Tipe Jigsaw Berbantuan Media Engklek Matematika Terhadap Kemampuan Komunikasi Matematis Siswa Kelas IV - Fadliansyah, Fauzi; Noviyanti, Elsa (LPPM Universitas Bina Bangsa, 2024)
This research shows that the application of the Jigsaw type cooperative learning model assisted by mathematical engklek media significantly improves students' mathematical communication abilities. After conducting an interview with the fourth grade teacher at SDN Cibeber III Cilegon with the initials